KOMPOSISI HASIL TANGKAPAN JARING TIGA LAPIS DI PERAIRAN SUAK SEUMASEH KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Muhammad Ghazali (Jurnal Perikanan Terpadu, 2018)
The fisheries sector is one of the exellence sectors in the West of Aceh. Generally, mostly fishermen have the trammel net that used in fishing operation. The trammel net is a fishing gear that used in the sea bottom for catching a lot of shrimps. The aiming of this research is to analyse catches composition of the trammel net. The research method that used was an experimental fishing. The results showed that catches composition of trammel net are 14 species  including Metapenaeus affinis, Fenneropenaeus merguiensis, Aristaeomorpha foliacea, Harpodon nehereus, Sphyrna lewini, Rastrelliger sp, Selar crumenophthalmus, Caesio chrysozon, Cynoglossus lingua, Thryssa setirostris, Terapon jarbua, Cyclocheilichthys armatus, Leiognathus equulus and Rachycentron canadum. Based on the catches composition are Leiognathus equulus are dominant with 19.37%, Metapenaeus affinis with 15.50%, and Aristaeomorpha foliacea 11.62%. Moreover, the rare species including  Hammerheads (Sphyrna lewini) and mackerel (Rastrelliger sp) as much as 0.77%. Sampling result also  obtained  amount of individuals as much as 129 individuals including 38 species target (shrimps) with 29.45% and non target species as much as 91 with 70.54%.Keywords : Trammel Net, Suak Seumaseh, West Aceh, Catch Composition